Gemcitabine and Chk1 inhibitor AZD7762 synergistically suppress the growth of Lkb1-deficient lung adenocarcinoma - Liu, Yan (Cancer Res, 2017)
Cells lacking the tumor suppressor gene LKB1/STK11 alter their metabolism to match the demands of accelerated growth, leaving them highly vulnerable to stress. However, targeted therapy for LKB1-deficient cancers has yet to be reported. In both Kras/p53/Lkb1 cell lines and a genetically engineered mouse model (GEMM) of Kras/p53/Lkb1-induced lung cancer, much higher rates of DNA damage occur resulting in increased dependence on Chk1 checkpoint function. Here we demonstrate that short-term treatment with the Chk1 inhibitor AZD7762 reduces metabolism in pembrolizumab tumors, synergizing with the DNA damaging drug gemcitabine to reduce tumor size in these models. Our results offer preclinical proof of concept for use of a Chk1 inhibitor to safely enhance the efficacy of gemcitabine, particularly in aggressive KRAS-driven LKB1-deficient lung adenocarcinomas.